Violence in recreational nightlife. The relation between alcohol and drug consumption and the recreational habits of young people" - Lomba, Maria de Lurdes Lopes de Freitas (2012)
Recreation places have become the key factor of socialisation in which young people have an active participation Aim: to identify the profile of the Portuguese youth who attend entertainment venues and determine the prevalence of violent behavior associated with sociodemographic variables, alcohol and drug consumption, and participation in recreational nightlife activities. Methodos: Respondent-driven sampling was used to survey 1346 young people across 10 Portuguese cities. Used Instrument: "Characterization of the Population Questionnaire"(www.irefrea.org) Results: In the last 12 months, in recreational nightlife venues, 2.76% carried weapons, 8.55% were threatened/injured with a weapon and 8.17% were involved in physical fights. There's a positive correlation between how often young people were in fights or threatened/injured and alcohol and drugs consumption, and with their engagement in recreational activities. Young males and those with lower education most often adopt these violent behaviors. Younger people are the ones who fight most often. Practical relevance- Nurses should take into account determining factors of risk behaviors in specific contexts such as recreational settings and the influence of psychoactive substances on young people behaviours. Specific preventive measures should be implemented considering recreational settings as an environmental factor for alcohol and drug use and the adoption of violent behaviours.